2017
DOI: 10.1038/srep41473
|View full text |Cite
|
Sign up to set email alerts
|

Kynurenine pathway metabolomics predicts and provides mechanistic insight into multiple sclerosis progression

Abstract: Activation of the kynurenine pathway (KP) of tryptophan metabolism results from chronic inflammation and is known to exacerbate progression of neurodegenerative disease. To gain insights into the links between inflammation, the KP and multiple sclerosis (MS) pathogenesis, we investigated the KP metabolomics profile of MS patients. Most significantly, we found aberrant levels of two key KP metabolites, kynurenic acid (KA) and quinolinic acid (QA). The balance between these metabolites is important as it determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
229
3
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 200 publications
(253 citation statements)
references
References 39 publications
17
229
3
4
Order By: Relevance
“…Here, we showed that higher relative abundance of kynurenine in the serum is associated with higher relapse rate in pediatric patients with MS. Unlike the previous report,16 we did not find a correlation between other kynurenine pathway metabolites and the risk of developing MS or physical or cognitive disability scores in our cohorts. This discrepancy might be due to the difference in the age of participants (pediatric vs. adult) or statistical modeling (e.g.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Here, we showed that higher relative abundance of kynurenine in the serum is associated with higher relapse rate in pediatric patients with MS. Unlike the previous report,16 we did not find a correlation between other kynurenine pathway metabolites and the risk of developing MS or physical or cognitive disability scores in our cohorts. This discrepancy might be due to the difference in the age of participants (pediatric vs. adult) or statistical modeling (e.g.…”
Section: Discussioncontrasting
confidence: 99%
“…Finally, higher kynurenine levels were associated with higher relapse rate. These results are generally in line with our understanding of the effects of different tryptophan metabolites on the risk and severity of MS 13, 14, 16. While metabolomics analyses have identified alterations in multiple metabolic processes in MS, these techniques have not been previously applied to pediatric MS and have not studied the tryptophan pathway as a whole 30.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Conversely, raising kynurenic acid levels in the CNS by inhibiting the enzyme kynurenine‐3‐monoxygenase (Forrest et al ) has overall neuro‐inhibitory and neuroprotective effects which are potentially of value in the treatment of neurodegenerative disorders, especially Huntington's disease (Stone ; Stoy et al ; Giorgini et al, , ; Guidetti et al ; Forrest et al ; Schwarcz et al ; Stone et al ,b; Lovelace et al ; Jacobs et al, ). Kynurenine metabolites, especially quinolinic acid and kynurenic acid may also be involved in the brain damage resulting from cerebral infarcts (strokes), and may be involved in dysfunctional conditions such as multiple sclerosis (Lovelace et al , ; Lim et al ).…”
Section: Introduction: the Kynurenine Pathway And Receptorsmentioning
confidence: 99%
“…The kynurenines produced by Trp catabolism may be neuroprotective (kynurenic acid, picolinic acid) or neurotoxic (3‐hydroxykynurenine, quinolinic acid), with dysfunction suggested in MS by greater activity in pathways leading to production of neurotoxic mediators 22. With measurement of greater IDO1 mRNA in cells from patients with CIS, the present study suggests greater flux through the kynurenine pathway early in the MS disease course.…”
Section: Discussionmentioning
confidence: 61%